Acute interstitial pneumonia, bovine respiratory disease complex and potential pneumotoxicity in feedlot cattle - Loneragan, Guy Heaton, author; Morley, P. S., advisor; Gould, Daniel H., advisor; Garry, Franklyn, committee member; Dargatz, David A., committee member (Colorado State University. Libraries, 2001)
The broad aims of these studies were to describe trends in mortalities, and evaluate a potential role of 3-methylindole (3MI) or its pneumotoxic metabolite, 3-methyleneindolenine (3 MEIN), in acute interstitial pneumonia (AIP) and bovine respiratory disease complex (BRD) in feedlot cattle. A retrospective cohort study was performed using data collected by the USDA's National Animal Health Monitoring System to evaluate trends in mortalities in feedlot cattle. The study population included approximately 21.8 million cattle placed in 121 feedlots from 1994 through 1999. Frequency counts of mortalities were modeled using Poisson regression. The mortality ratio was 12.6 deaths per 1,000 placements. The risk of feedlot mortalities increased from 1994 through 1999 because of increases in the proportion of animals that died from respiratory disorders. Prospective case-control studies were performed to evaluate potential causes of AIP. Lung and blood samples were collected from animals from 14 feedlots located in CO, NE, KS and TX. Histological diagnoses were categorized as AIP cases, bronchopneumonia (BP) cases, and controls. Acute interstitial pneumonia cases had been at the feedlot for an average of 127.2 days, which was longer than BP cases (98.6 days) and controls (84.0 days). The presence of a viral respiratory pathogen was not associated with histological category. Bovine respiratory syncytial virus was detected in 8.3% of AIP cases and 24.0% of controls. Histological category was associated with isolation of an aerobic bacteria and mycoplasma. Bronchopneumonia cases were at greater risk for aerobic bacteria and mycoplasma isolation compared to AIP cases and controls. Lung 3MEIN-adduct concentrations were greater in AIP (P < 0.01) and BP (P < 0.01) cases compared to controls. Blood 3MEIN-adduct concentrations were greater in AIP-affected animals than controls (P < 0.01) or animals with BP (P = 0.02). The odds of an AIP case being a heifer was 3.1 times greater than the odds of an AIP case being a steer. Time-dependent patterns and magnitudes of plasma 3-methylindole and blood 3MEIN-adduct concentrations in feedlot cattle were described using 64 single-source yearling steers in a completely randomized study design with repeated measures. Blood samples were collected from all steers approximately 4 times per week for 3 weeks, 3 times per week for the following 5 weeks, then weekly for an additional 10 weeks. All plasma samples were analyzed for 3MI concentrations. Blood samples collected during the first 8 weeks from 32 animals were analyzed for 3MEIN-adduct concentration. Blood 3MEIN-adduct concentrations peaked during the period of greatest risk of the BRD complex. Conversely, plasma 3MI concentrations decreased during the same period. The effect of dietary inclusion of aspirin and vitamin E on plasma 3MI concentration, blood and lung 3MEIN-adduct concentration, occurrence of grossly identifiable lung lesions at harvest, and animal performance was evaluated. Two trials were conducted concurrently using steers (316 kg) obtained from a single source. Sixty-four animals were used in trial 1, and 192 animals were used in trial 2. A 2x2 factorial treatment design was used in each trial and treatment factors were aspirin (0 or 3 g PO daily), and supplemental vitamin E (0 or 1,500 iu PO daily). Animals from trial 1 were harvested on day 59. 3-methylindole concentration was measured in plasma and 3MEIN-adduct concentration was determined in blood and lung tissue. Trial 2 animals were weighed every 28 days and harvested on day 138. Vitamin E was associated with an increased concentration of plasma 3MI (P = 0.08). Without supplemental vitamin E, aspirin was associated with increased blood 3MEIN-adduct concentration (P = 0.01). of trial 1 animals, 57.1 % had grossly identifiable lesions at harvest although none were observed to be sick. The presence of lung lesions was not associated with adverse effects on carcass characteristics, 3MI and 3MEIN concentrations, or treatment. Nor was treatment associated with improvements or adverse effects in body weight, mean daily weight gain, dry matter intake, or feed conversion in trial 2. An increasing proportion of placements died from respiratory tract disorders from 1994 through 1999. Increased pulmonary generation of the pneumotoxin 3MEIN, may be important in the pathogenesis of AIP. Additionally, 3MEIN-adduct concentrations were elevated during the period temporally associated with greatest risk for BRD.